Laparoscopic approach for removing a coin trapped in Meckel's diverticulum - KIYAN, GÜRSU; ERBARUT SEVEN, İPEK; KARADENİZ CERİT, KIVILCIM (TURKISH ASSOC TRAUMA EMERGENCY SURGERY, 2017)
Foreign body ingestion is a common problem in children. Most of these foreign bodies spontaneously pass through the gastrointestinal tract. When there is a persistent foreign body in the abdomen, it is impossible to make a diagnosis without exploration. We herein present the case of a child who was admitted to our hospital with a coin trapped in Meckel's diverticulum and our laparoscopic approach in this case. The diagnosis of Meckel's diverticulum should be considered when there is a prolonged lodgment of a foreign body in the right lower quadrant, and the laparoscopic approach is the preferred choice in these cases.
Keywords: Child; coin; Meckel's diverticulum; FOREIGN-BODY INGESTION; PERFORATION; CHILDREN